Given a $2\rightarrow2$ body scattering problem in CM frame, i.e., $\gamma_1\gamma_2\rightarrow\gamma_3\gamma_4$ process, and the coordinate is chosen such that $\gamma_1$ is moving along $+z$-axis, with scattering angle $\theta$ of $\gamma_3$ in the $xz$-plane.

Then the polarization vectors for for $\gamma_1$ is by convention:

\begin{align} \hat{e}_+&=-\frac{1}{\sqrt{2}}(\hat{x}+i\hat{y})\\ \hat{e}_-&=\frac{1}{\sqrt{2}}(\hat{x}-i\hat{y}) \end{align}

and for $\gamma_3$, one just needs to apply $R_y(\theta)$ on the vectors above.

However, how do I find the polarization vectors for $\gamma_2$ and $\gamma_4$, where they have momentum $\vec{k}_2=-\vec{k}_1$ and $\vec{k}_3=-\vec{k}_4$?

My idea is to apply a rotation in $y$-direction with angle $\pi$ and $\pi-\theta$ on polarization vectors of $\gamma_1$ and $\gamma_3$ correspondingly.

In short, the question would be how to find the polarization vectors with inverted momentum $\vec{k}$?


1 Answer 1


The polarization vectors for any photon in the $xz$-plane* whose momentum vector makes an angle $\vartheta$ with the $z$-axis are those obtained from rotating $\hat{e}_{+}=\hat{e}^{(1)}_{+}$ and $\hat{e}_{-}=\hat{e}^{(1)}_{-}$ with $R_{y}(\vartheta)$. Since the momentum $\vec{k}_{2}$ of the second incoming photon points in the direction opposite ($180^{\circ}$ away from) $\vec{k}_{1}$, the right- and left-circular polarization vectors for $\gamma_{2}$ are \begin{align} \hat{e}^{(2)}_{+}=R_{y}(\pi)\hat{e}^{(1)}_{+} & =-\frac{1}{\sqrt{2}}(-\hat{x}+i\hat{y})=\hat{e}^{(1)}_{-} \\ \hat{e}^{(2)}_{-}=R_{y}(\pi)\hat{e}^{(1)}_{-} & =\frac{1}{\sqrt{2}}(-\hat{x}-i\hat{y})=\hat{e}^{(1)}_{+}. \end{align} So for a photon traveling the opposite direction, the roles of the two circular polarization vectors are interchanged. This uses, that $R_{y}(\pi)\hat{x}=-\hat{x}$ and $R_{y}(\pi)\hat{y}=\hat{y}$.

The relationship between the helicity basis polarization vectors for $\gamma_{3}$ and $\gamma_{4}$ is the same: \begin{align} \hat{e}^{(4)}_{+}=R_{y}(\pi)\hat{e}^{(3)}_{+} & =R_{y}(\pi)R_{y}(\theta)\hat{e}^{(1)}_{+}=R_{y}(\pi+\theta)\hat{e}^{(1)}_{+}=\hat{e}^{(3)}_{-} \\ \hat{e}^{(4)}_{-}=R_{y}(\pi)\hat{e}^{(3)}_{-} & =R_{y}(\pi)R_{y}(\theta)\hat{e}^{(1)}_{-}=R_{y}(\pi+\theta)\hat{e}^{(1)}_{-}=\hat{e}^{(3)}_{+}. \end{align}

*You can always choose coordinates for the $2\rightarrow2$ process so it likes in the $xz$-plane.

  • $\begingroup$ Thanks @Buzz. I also figured out why I had \pi-\theta instead of \pi+\theta. $\endgroup$ Commented Dec 30, 2020 at 6:23

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.